CalliSpheres Drug-Eluting Bead Transcatheter Arterial Chemoembolization Presents With Better Efficacy and Equal Safety Compared to Conventional TACE in Treating Patients With Hepatocellular Carcinoma. (19th July 2019) - Xiang, Hua; Long, Lin; Yao, Yuanhui; Fang, Zhiyong; Zhang, Zhiming; Zhang, Yongjin
The aim of this study was to compare the treatment response, survival, liver function, and adverse event incidence of drug-eluting bead transcatheter arterial chemoembolization using CalliSpheres microspheres with conventional transcatheter arterial chemoembolization in patients with hepatocellular carcinoma. Seventy-three patients with hepatocellular carcinoma who received drug-eluting bead transcatheter arterial chemoembolization (using CalliSpheres microspheres) or conventional transcatheter arterial chemoembolization treatment were consecutively enrolled. Treatment response was assessed by modified Response Evaluation Criteria in Solid Tumors at month 1/month 3/month 6; posttreatment, liver function indexes, and adverse events were recorded. Progression-free survival and overall survival were also calculated. Objective response rate of patients at months 1, 3, and 6, disease control rate of patients and objective response rate of nodules at month 3 were increased in drug-eluting bead transcatheter arterial chemoembolization group compared with conventional transcatheter arterial chemoembolization group. In addition, drug-eluting bead transcatheter arterial chemoembolization using CalliSpheres microspheres was an independent factor for predicting better objective response rate at month 1. Patients in drug-eluting bead transcatheter arterial chemoembolization group achieved longer progression-free survival and similar overall survival compared to those in conventional transcatheter arterial chemoembolization group; Cox proportional hazards regression model analyses revealed that drug-eluting bead transcatheter arterial chemoembolization using CalliSpheres microspheres was associated with better progression-free survival while it did not affect overall survival. Meanwhile, most of the occurrences of abnormal liver function indexes were similar between 2 groups, whereas drug-eluting bead transcatheter arterial chemoembolization group had a higher percentage of patients with total bile acid ≥2 upper limit of normal compared to conventional transcatheter arterial chemoembolization group at month 1. Moreover, the adverse event incidences between 2 groups were similar. In conclusion, drug-eluting bead transcatheter arterial chemoembolization using CalliSpheres microspheres achieves better treatment response and progression-free survival while equal safety compared to conventional transcatheter arterial chemoembolization in patients with hepatocellular carcinoma.